2021
DOI: 10.1590/1678-4324-2021200574
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Gametogenesis of Biomphalaria glabrata (Mollusca, Gastropoda, Pulmonata): Implications for Histopathological Assessment

Abstract: The reproductive system has a fundamental role in population dynamics and several reproduction strategies have been shaped by the environment over time. Many environmental pressures are generated by releasing pollutants, as endocrine disruptors, that can affect the reproductive system of individuals, among them invertebrates. The freshwater snails Biomphalaria spp. are used as biomonitor in several ecotoxicological studies; however, there are few studies about gametogenesis and morphology of reproductive snail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The histological structures of the hermaphrodite gland of untreated T. pisana snails reported in this study showed different stages of spermatogenesis and oogenesis in addition to highlighting the follicular and germinal layers with their cells. Similar structures were illustrated by Morad (2021) for hermaphrodite gland of Eobania vermiculata snails and Rodrigues et al. (2021) for that of Biomophalaria alexandrina .…”
Section: Discussionsupporting
confidence: 68%
“…The histological structures of the hermaphrodite gland of untreated T. pisana snails reported in this study showed different stages of spermatogenesis and oogenesis in addition to highlighting the follicular and germinal layers with their cells. Similar structures were illustrated by Morad (2021) for hermaphrodite gland of Eobania vermiculata snails and Rodrigues et al. (2021) for that of Biomophalaria alexandrina .…”
Section: Discussionsupporting
confidence: 68%
“…6 , Table S16 ). In the developing ovotestis of juvenile snails, a strong early expression of genes involved in spermatogenesis might be expected because B. glabrata is a functionally protandrous species [ 61 ], and the number of cells involved in spermatogenesis is much greater than in oogenesis [ 62 ], so would be easier to detect.…”
Section: Resultsmentioning
confidence: 99%